The Copernican revolution planetary astronomy in the development of Western thought - Kuhn, Thomas S. (Cambridge Harvard University Press, 1957)
"The author brings to a common focus the considered approach of the historian, the technical understanding of the scientist and the skill and experience of an able teacher. No careful reader of this well-wrought volume can fail to appreciate the nicely balanced interplay of these elements in the full explication of one of the major turning points in the evolution of scientific thought. For those concerned with the teaching of the history of science, this discussion of the issues involved in the Copernican revolution will prove to be indispensable, a superb analysis of the anatomy of revolution. Those drawn to the question of meaning which the historian of science can give to the evolution of ideas will find this book equally valuable, a paradigm of synthesis and interpretation"--[Isis]
The ancient two-sphere universe -- The problem of the planets -- The two-sphere universe in Aristotelian thought -- Recasting the tradition: Aristotle to the Copernicans -- Copernicus' innovation -- The assimilation of Copernican astronomy -- The new universe.
Includes bibliographical references (pages [279]-281) and index.
Keywords: Copernicus, Nicolaus -- 1473-1543.; Cosmology